KEY SUCCESS FACTORS THE IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEMS (CASE STUDY: PT PQR) - Uriawan, Wisnu; Melindah, Devi; Fitri Andriani, Arisyah; Pratiwi Awaliah, Resti (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2025)
Innovation in Accounting Information Systems (AIS) is able to encourage companies to improve their performance in terms of financial management. Accounting Information Systems (AIS) in the modern financial sector are used to manage company financial transaction data. This research examines the keys to success in utilizing AIS at PT PQR. On the app Enterprise Resource Planning (ERP), AIS is part of managing company financial data. PT PQR as a company operating in the telecommunications sector that manages many transactions is very suitable to develop AIS. This research uses a qualitative approach through literature study. Data was obtained through collecting, analyzing and interpreting the keys to successful implementation of AIS at PT PQR. The research results show that there are 7 (seven) main factors that most influence the success of AIS. The 7 (seven) factors include: organizational culture, information technology, application of accounting information, manager participation, manager accounting knowledge, manager information technology knowledge, and consultation with experts.